MANAGEMENT AND COLLECTION OF MONEY WAQF AT THE BAITUL ASYI WAQF FOUNDATION: A Study of the Implementation of Money Waqf Law Based on Islamic Law - Mira Amelia; Mizaj Iskandar; Muslim Abdullah (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
The Baitul Asyi Waqf Foundation is one of the leading waqf institutions in Aceh, known for its active role in collecting and managing cash waqf. This study aims to examine the cash waqf collection strategies and management systems implemented by the Baitul Asyi Waqf Foundation. This study employs a qualitative research method with a normative legal research approach, utilizing secondary data in the form of primary legal materials and a review of Islamic legal literature. The study findings indicate that the foundation adopts a strategy based on community trust, transparency, and professionalism in managing endowment funds. Additionally, the use of information technology and collaboration with banks that entrust their endowment funds to be managed by the Baitul Asyi Endowment Foundation aims to ensure that endowment funds are managed by trustees, with the proceeds utilised for public or social purposes to enhance the effectiveness of fund collection. In terms of management, endowment funds are invested in productive sectors, such as property and Sharia-based businesses, with the proceeds used to assist Aceh Hajj pilgrims, education, and other social services. This study concludes that the management of monetary endowments is permissible under Islamic law, and according to the various schools of thought, monetary endowments are permissible.